Soil fertility and bean nutrition in Uganda: A review and future research needs - Ochwoh, Víctor A.; Wortmann, Charles S. (International Center for Tropical Agriculture, 1991)
Results of research on soil fertility management for bean production in Uganda are explored. The occurrence and severity of soil fertility problems as constraints to bean production are examined and additional research needs are suggested. Results of trials conducted on research station and farmers' fields show that soil nutrition problems are major contraints in bean production. Yield response to applied N and P frequently occur. Application of K and lime result in increased yield in selected sites, but response to applied micro-elements are rare. Crop production in Uganda is concentrated on the more productive soils. Much of the potentially arable land is not in cultivation because of low soil fertility problems. Other areas are extensively cultivated, but with frequent fallow periods. Soil fertility problems can be expected to increase as crop production encroaches into marginal areas. (AS)